2014
DOI: 10.1186/1556-276x-9-339
|View full text |Cite
|
Sign up to set email alerts
|

The role of Si interstitials in the migration and growth of Ge nanocrystallites under thermal annealing in an oxidizing ambient

Abstract: We report a unique growth and migration behavior of Ge nanocrystallites mediated by the presence of Si interstitials under thermal annealing at 900°C within an H2O ambient. The Ge nanocrystallites were previously generated by the selective oxidation of SiGe nanopillars and appeared to be very sensitive to the presence of Si interstitials that come either from adjacent Si3N4 layers or from within the oxidized nanopillars. A cooperative mechanism is proposed, wherein the Si interstitials aid in both the migratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(63 citation statements)
references
References 17 publications
2
61
0
Order By: Relevance
“…1b. We have previously proposed [18, 20] that this thin, interfacial SiO 2 layer between the Ge QD and the SiGe shell is formed by the thermal oxidation of Si interstitials. These interstitials are released from the dissociation of the Si substrate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1b. We have previously proposed [18, 20] that this thin, interfacial SiO 2 layer between the Ge QD and the SiGe shell is formed by the thermal oxidation of Si interstitials. These interstitials are released from the dissociation of the Si substrate.…”
Section: Resultsmentioning
confidence: 99%
“…We also place these QDs at desired spatial locations with controlled depths of penetration into Si. This was achieved using the exquisite control available through lithographic nanopatterning and selective oxidation of the nanopatterned SiGe layers [1720]. Remarkably, such self-aligned heterostructures of SiO 2 /Ge QD/SiO 2 /SiGe shell over the Si substrate can be created in a single fabrication step.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous results (Chien et al, 2011;Kuo et al, 2012;Wang et al, 2013;Chen et al, 2014;Lai et al, 2015) have shown that thermal oxidation performed on poly-Si0.85Ge0.15 nano-pillar structures preferentially converts the Si from the poly-Si0.85Ge0.15 to SiO2, leading to the formation of a single Ge dot within each oxidized nano-pillar through an unusual Ostwald Ripening process consolidating the segregated Ge nanocrystallites (Chien et al, 2011). Interestingly, excess thermal oxidation (or thermal annealing) of 15-65 min enables the as-formed Ge dot to penetrate the underlying, buffer Si3N4 layer, and ultimately form a 2-15-nm-thick Si1−xGex-shell layer (x > 0.5) with a "cup"-shape morphology near the top surface of the Si substrate when the Ge dot comes in close proximity to the Si substrate.…”
Section: Resultsmentioning
confidence: 99%
“…Our previously reports (Kuo et al, 2012;Chen et al, 2014;Lai et al, 2015) have described that the interfacial SiO2 thickness is determined by an exquisitely controlled dynamic balance that exists between the fluxes of oxygen and Si interstitials. Thus, judicial control of either the source of Si interstitials or the flux of oxygen interstitials by changing thermal annealing conditions during the penetration of Ge dot effectively controls the interfacial SiO2 thickness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation